2018
DOI: 10.3389/frobt.2018.00112
|View full text |Cite
|
Sign up to set email alerts
|

“We Wait”—The Impact of Character Responsiveness and Self Embodiment on Presence and Interest in an Immersive News Experience

Abstract: A virtual reality scenario called "We Wait" gives people an immersive experience of the plight of refugees waiting to be picked up by a boat on a shore in Turkey to be illegally taken to Europe, crossing a dangerous stretch of sea. This was based on BBC news reporting of the refugee situation, but deliberately depicted as an animation with cartoon-like characters representing the refugees. Of interest was the level of presence that might be experienced by participants and the extent to which the scenario might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 58 publications
1
43
0
3
Order By: Relevance
“…Plausibility is the illusion that what is happening in the environment is really happening. A number of questions, based on Steed, et al 63 (and many previous studies) were administered after the Shocks scenario, shown in Table 1. Figure 8 shows the box plots of the scores on these questions.…”
Section: Results Of the Model A Summary Of The Results For All Parammentioning
confidence: 99%
“…Plausibility is the illusion that what is happening in the environment is really happening. A number of questions, based on Steed, et al 63 (and many previous studies) were administered after the Shocks scenario, shown in Table 1. Figure 8 shows the box plots of the scores on these questions.…”
Section: Results Of the Model A Summary Of The Results For All Parammentioning
confidence: 99%
“…A final relevant element in extant IJ research is empathy. In a 2015 TED talk, filmmaker Chris Milk described VR as 'the ultimate empathy machine', and it caught a lot of interest in VR technology's potential for news (Steed et al, 2018). The Tow Report Virtual Reality Journalism pointed out that 'a core question is whether VR can provide similar feelings of empathy and compassion to real-life experiences' (Aronson-Rath et al, 2015).…”
mentioning
confidence: 99%
“…Partiendo del hecho de que la realidad virtual y los formatos multimedia con capacidad inmersiva generan mayor interés y vinculación de la audiencia, esencialmente con determinados temas, como se desprende de experimentos como los de Shin y Biocca (2018) o de Steed et al (2018), la principal pretensión de esta investigación es contribuir, por consiguiente, a una aproximación de un modelo o propuesta estándar narrativa para la creación de contenidos multimedia con capacidad inmersiva en el ámbito del periodismo.…”
Section: Objetivos E Hipótesisunclassified
“…El tamaño de la muestra va en sintonía con estudios relacionados con la misma tecnología y similar estilo narrativo (Aardena et al, 2010;Aitamurto, 2018;Hendriks et al, 2019;Jones, 2017;Matsangidou et al, 2019y Steed et al, 2018.…”
Section: Metodologíaunclassified